Croquer le travail : une commande du CEA - Michèle Dupré (Images du Travail, Travail des Images)
This article revisits the key theme of the journal ITTI, namely the relationship between the work of images and the images of work. The questions: who paints what work, where and how are again developed here by showing the singular interaction between a commission made by a large organization to a painter, external to this world of work. It consists of sketching thirty jobs in a CEA department at a time when a skills management tool is also being developed.